Advances in water research: enhancing sustainable water use in irrigated agriculture in South Africa - Nhamo, L.; Mpandeli, S.; Liphadzi, S.; Hlophe-Ginindza, S.; Kapari, M.; Molwantwa, J.; Mabhaudhi, Tafadzwanashe (Elsevier, 2023)
Water scarcity has become one of the greatest challenges facing humankind today. Its scarcity is compounded by climate change and increasing demand from a growing population. In South Africa, over 60% of the available freshwater resources are used in agriculture, mainly in irrigated agriculture. There is an urgent need to promote sustainable irrigation technologies that optimize food production without increasing water applied and with positive environmental spinoffs. Sustainable irrigation technologies and practices could enhance water use efficiency (WUE) and productivity in agriculture and reduce environmental burdens, including energy use. This chapter highlights some of the innovative irrigation practices and technologies that enhance food production and, at the same time, reduce water use in agriculture. The chapter broadly discusses WUE and water productivity (WP) in irrigated agriculture from engineering and agronomic perspectives. The chapter further highlights some of the environmental impacts of irrigation expansion and the possible solutions. We further provide the importance of accurate spatial information on irrigated areas to inform policy on irrigation expansion. The Water Research Commission (WRC) of South Africa has been spearheading research on the sustainable use of water for the past 50 years as part of its research agenda.